2021
DOI: 10.1002/lno.11747
|View full text |Cite
|
Sign up to set email alerts
|

Ecological resilience in tropical Andean lakes: A paleolimnological perspective

Abstract: Little is known about whether changes in lake ecosystem structure over the past 150 years are unprecedented when considering longer timescales. Similarly, research linking environmental stressors to lake ecological resilience has traditionally focused on a few sentinel sites, hindering the study of spatially synchronous changes across large areas. Here, we studied signatures of paleolimnological resilience by tracking change in diatom community composition over the last 2000 years in four Ecuadorian Andean lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Tadpole grazing effects were not completely replaceable by compensatory responses from insects, and shifts in grazing effects were not uniform across habitats. This study also points to a topic considered in several other papers about changes in biodiversity and its consequences (e.g., Benito et al 2022; Li et al 2022; Rii et al 2022). Resilience is often tied to biodiversity, and the rapid loss of species from aquatic systems, particularly lakes and rivers, suggests widespread loss of resilience.…”
Section: The Transition From Theoretical To Empirical Sciencesupporting
confidence: 72%
See 2 more Smart Citations
“…Tadpole grazing effects were not completely replaceable by compensatory responses from insects, and shifts in grazing effects were not uniform across habitats. This study also points to a topic considered in several other papers about changes in biodiversity and its consequences (e.g., Benito et al 2022; Li et al 2022; Rii et al 2022). Resilience is often tied to biodiversity, and the rapid loss of species from aquatic systems, particularly lakes and rivers, suggests widespread loss of resilience.…”
Section: The Transition From Theoretical To Empirical Sciencesupporting
confidence: 72%
“…In this volume, long‐term studies of larger and deeper lakes reveal regimes of water clarity and phytoplankton related to food web shifts in a north temperate lake (Trout Lake, Wisconsin, USA) (Martin et al 2022) and to climate‐driven changes in the inputs of colored dissolved organic carbon in a subtropical lake (Lake Annie, Florida, USA) (Sullivan et al 2022). Collectively these studies of regime shifts, as well as others presented in this volume (e.g., Benito et al 2022), indicate that ecosystems under the influence of changing internal and external forces can move quickly to a different and long‐lasting state, affecting ecosystem services. The studies expand our understanding of the causes of resilience, the places where regime shifts occur, and highlight the value of long‐term data.…”
Section: Application To Diverse Systemssupporting
confidence: 61%
See 1 more Smart Citation
“…In the absence of long-term observational and monitoring data from the CNP, sediments from these lakes have been used as natural archives to gain insights into aquatic ecological shifts since the Industrial Revolution (Michelutti et al, 2015;Benito et al, 2022). Fossil diatom assemblages obtained from these lacustrine sediments have revealed abrupt replacements of species in the past ∼50 yr. Based on the assumption that the lakes are pristine and isolated from direct human activities in their catchments, it was suggested that rising temperatures and longer periods of thermal stratification in the lakes are the main mechanisms behind elevated abundances of certain diatom taxa (Michelutti et al, 2015(Michelutti et al, , 2016.…”
Section: Climate and Sedimentation In El Cajas Ecuadormentioning
confidence: 99%
“…However, less is known about the detailed defense mechanisms involved in the UV-B response in microalgae, especially in those native strains adapted to extreme and unexplored ecosystems. For instance, the high Andean lakes are a still unexplored source of photosynthetic microorganisms that are well adapted to extreme environmental conditions characteristic of the equatorial zone, such as altitude, high UV radiation, constant temperatures, and constant photoperiods [ 20 ]. Therefore, the aim of the present study was to investigate the differential effects of UV-B on the inhibition or activation of protective mechanisms in native microalgae from highland, lowland, and indoor conditions under an eco-physiological context.…”
Section: Introductionmentioning
confidence: 99%